2021
DOI: 10.1111/jth.15438
|View full text |Cite
|
Sign up to set email alerts
|

International multicenter, multiplatform study to validate Taipan snake venom time as a lupus anticoagulant screening test with ecarin time as the confirmatory test: Communication from the ISTH SSC Subcommittee on Lupus Anticoagulant/Antiphospholipid Antibodies

Abstract: Background Lupus anticoagulant (LA) assays are compromised in anticoagulated patients, and existing strategies to overcome the interferences have limitations. The prothrombin‐activating Taipan snake venom time (TSVT) screening test and ecarin time (ET) confirmatory test are innately insensitive to vitamin K antagonists (VKA) and direct factor Xa inhibitors (DFXaI). Objectives Validate standardized TSVT/ET reagents for LA detection, in a multicenter, multiplatform study. Patients/Methods Six centers from four c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 77 publications
2
54
0
Order By: Relevance
“…The TSVT has been previously investigated as a method to detect an LA in patients on DFXaIs. 10 , 13 , 18 , 19 , 20 , 21 The advantage of a TSVT/ET assay is that no preanalytical inactivation step is necessary for LA detection on DFXaI because prothrombin activation bypasses the effects of factor Xa inhibitors. 13 The ISTH has previously issued guidance within this area and concluded that there was “no conclusive independent evidence reported on their diagnostic efficacy” and that studies had small numbers of patients mostly on rivaroxaban with challenges in kit standardization and availability likely to limit widespread utility and generalizability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The TSVT has been previously investigated as a method to detect an LA in patients on DFXaIs. 10 , 13 , 18 , 19 , 20 , 21 The advantage of a TSVT/ET assay is that no preanalytical inactivation step is necessary for LA detection on DFXaI because prothrombin activation bypasses the effects of factor Xa inhibitors. 13 The ISTH has previously issued guidance within this area and concluded that there was “no conclusive independent evidence reported on their diagnostic efficacy” and that studies had small numbers of patients mostly on rivaroxaban with challenges in kit standardization and availability likely to limit widespread utility and generalizability.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 13 , 18 , 19 , 20 , 21 The advantage of a TSVT/ET assay is that no preanalytical inactivation step is necessary for LA detection on DFXaI because prothrombin activation bypasses the effects of factor Xa inhibitors. 13 The ISTH has previously issued guidance within this area and concluded that there was “no conclusive independent evidence reported on their diagnostic efficacy” and that studies had small numbers of patients mostly on rivaroxaban with challenges in kit standardization and availability likely to limit widespread utility and generalizability. 6 This has recently been challenged in a multicenter, multiplatform publication by the ISTH SSC Subcommittee on Lupus Anticoagulant/Antiphospholipid Antibodies, which validated the TSVT/ET for patients taking DFXaI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[170][171][172] A recent multi-centre study has validated TSVT/ET testing in non-anticoagulated patients and those anticoagulated with VKAs and all DFXaIs. 173 Although adsorbents for direct oral anticoagulant (DOAC) removal from plasma are available, they have their own limitations, and cannot mitigate for the effects of VKA anticoagulation. 158,174,175 Of potential clinical import is that T/E ratio and TSVT/ET testing have been reported to detect small numbers of LA unreactive in dRVVT and aPTT.…”
Section: Lupus Anticoagulantsmentioning
confidence: 99%